Standardization and the Stability of Collusion - Luca Lambertini; Sougata Poddar; Dan Sasaki (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 1997)
We characterize the interplay between firms' decision in terms of product standardization and the nature of their ensuing market behaviour. We prove the existence of a non-monotone relationship between firms' decision at the product stage and their intertemporal preferences.
Keywords: 330